PERENCANAAN ULANG STRUKTUR GEDUNG LIMA LANTAI ASRAMA HAJI SEMARANG - Majid, Ricky Abdul; Zhafira, Talitha; Umar, Wahyu Khoirul; Purwanto, Purwanto (Jurnal Teknik Sipil Giratory UPGRIS, 2023)
Due to the increasing number of Hajj pilgrims, the need for accommodating them has also risen. Therefore, a redesign is necessary to enhance the capacity of accommodating the pilgrims. The Analysis and Structural Planning of the Hajj Dormitory Semarang using ETABS software in compliance with the Indonesian National Standard (SNI). The redesign of the Hajj dormitory aims to augment the housing capacity for prospective Hajj pilgrims. The Revised Structural Planning for the Five-Story Hajj Dormitory Building Semarang aims to analyze and redesign the structure of the dormitory. This involves utilizing concrete quality of 24.9 MPa for the upper structure and 30 MPa for the lower structure, with main reinforcement using 420 MPa, while secondary reinforcement uses 280 MPa. The structural analysis approach involves inputting geometric data, loads, and material characteristics, including desired concrete and steel qualities, into the ETABS software. The analysis adheres to the SNI guidelines governing building loads, seismic resilience, and other structural safety factors. The analysis results provide insight into the structural response spectrum, with a mass participation of UX 99.98% and UY 99.19%. Control Base Shear Vdynamic Vstatic, with Eq Dx Eq Sx and Eq Dy Eq Sy, is 8623.266 8563.3067 and 7928.0409 7722.4166. The maximum story displacement due to dynamic seismic motion in the X and Y directions is 14.33 mm and 15.95 mm. Meanwhile, the story drift with an Inelastic Drift value less than 61.5 mm for safety building permissible deviation. The largest permissible deviations obtained for the X and Y directions are 18.816 mm and 20.554 mm.